Incidence and Severity of Intra-Ventricular Hemorrhage (IVH) in Preterm Infants, Northeast of Iran - Fouladinejad, Mahnaz; Khorsand zak, Hadi; Nematollahi, Nematollah; Alaee, Ehsan (Journal of Nepal Paediatric Society, 2016)
Introduction: The incidence rate of Intra-Ventricular Haemorrhage (IVH) varies from 20% to 25% among preterm infants with a very low birth weight. IVH could compose critical disabilities which are directly associated to its grade. The aim of this study was to evaluate the incidence and severity of IVH in preterm infants referred to the academic Hospital of Gorgan, Northeast of Iran. Materials and Methods: In this cross-sectional study, we examined all preterm infants who had been referred to the academic Hospital of Gorgan, Northeast of Iran between Augusts 2014 and February 2015. Seventy one preterm infants (≤34 weeks of gestation, ≤1500g birth weight) have been included. Cranial ultrasound was done within 3-5 days of birth for all subjects and subsequent ultrasounds were performed based on their birth weight by portable ultrasound device. Results: The overall incidence of IVH was 64.8% in the present study. There was a significant relationship between IVH incidence and the gestational age (p=0.010). Also the lower birth weight was associated to the higher rate of IVH complications reported in sequential ultrasounds (p<0.05). Conclusion: Gestational age and birth weight seem to have key roles in the occurrence and severity of IVH, respectively. J Nepal Paediatr Soc 2016;36(1):38-41